Certain correspondence of the Foreign Office and of the Hudson's Bay Company [electronic resource] : copied from original documents, London 1898. - Klotz, Otto, 1852-1923.; Hudson's Bay Company.; Great Britain. Foreign Office. (Ottawa : Government Print. Bureau, 1899)
The documents were copied by Otto Klotz who was also responsible for their discovery in 1898--A bibliography of British Columbia / B.J. Lowther. Tables. At head of title: Confidential. "Department of the Interior, Office of Chief astronomer, November. 1899." Electronic reproduction. Mode of access: Internet. 44